1998
DOI: 10.1080/13855149809408787
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of powder factors for tunnel blasting using neural networks

Abstract: This paper presents a forecasting model for powder factors in tunnel blasting using artificial neural networks (ANN). Case data of a railway tunnel recently under construction in Taiwan were used to establish the model. The main rock type in the tested case was metamorphic rock. In this study, the rock mechanical factors influencing the powder factors were empirically identified first. Rock mechanical parameters having a significant influcncc were then filtered to train and test the ANN. The ANN model for pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…BEM back-analysis was utilized to calculate far-field stress state (Li et al 2009). In this paper, more efficient methods such as neural network-based techniques may be preferred over traditional methods (Jaiswal et al 2004;Lee and Sterling 1992;Leu et al 1998Leu et al , 2001Singh 2002, 2005;Monjezi et al 2006a;Monjezi and Dehghani 2008).…”
Section: Introductionmentioning
confidence: 97%
“…BEM back-analysis was utilized to calculate far-field stress state (Li et al 2009). In this paper, more efficient methods such as neural network-based techniques may be preferred over traditional methods (Jaiswal et al 2004;Lee and Sterling 1992;Leu et al 1998Leu et al , 2001Singh 2002, 2005;Monjezi et al 2006a;Monjezi and Dehghani 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Because the data that were used during this study were collected at a single tunnel construction site, so that the locations of the blastholes and ignition patterns were constant, the blasting conditions mentioned in this study were not required to be used as input parameters to the NN. The input parameters selected for this study, were based on those previously identified (Lilly, 1986;Scott, 1996;Leu et al, 1998Leu et al, , 2001. Fourteen input parameters were used to predict the powder factors.…”
Section: Nn Training and Parameter Determinationmentioning
confidence: 99%
“…In particular, NNs were applied to failure modes in tunnels by Lee and Sterling (1992), tunnel blasting by Leu et al (1998) and tunnel support by Leu et al (2001).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of tools have been developed in AI to solve the most difficult problems and ANN is one of them. Literature review indicates that a lot of work has been done on the application of ANN to predict various aspects of blast-induced ground vibrations [21][22][23][24], air overpressure [25], fly rock [26][27][28], back break [29][30][31][32], powder factor [33][34][35], estimation of blast geometry [36][37][38], estimation of fragmentation [32,[39][40][41][42][43][44][45] etc.…”
Section: Introductionmentioning
confidence: 99%